AN ANALYSYIS OF SPEAKING ANXIETY BY THE TENTH GRADE STUDENTS OF SMA NEGERI 1 BAUBAU - Wa Ode Hanafiah; Syamsul Una; Riezky Yulanda Putri (English Education Journal, 2023)
The problem statement of this research was what types and factors effecting the english-speaking anxiety of tenth grade students of SMA Negeri 1 Baubau. The objective of this research was to identify what types and factors effecting the speaking anxiety of grade tenth students of SMA Neeri 1 Baubau. This research used the qualitative research design. The subject of this research was the grade tenth students at SMA Negeri 1 Baubau in the odd semester 2022/2023. The data was obtained by observation and interview then was analyzed by the researcher with three steps: data reduction, data display, and draw conclusion or verification. This research found that there were three types and factors that effected the grade tenth students’ speaking anxiety of SMA Negeri 1 Baubau. For types anxiety there were communication apprehension, test anxiety, and fear of negative evaluation. And for factors anxiety, there were afraid of making mistakes, lack of vocabulary, and lack of confident.